Impact of COVID-19 Pandemic on students learning Anatomy-View Point - Syed Samiullah , Aiyesha Humaira (Journal of Rawalpindi Medical College, 2021)
The effect of Covid-19 pandemic on medical education is long lasting. Stakeholders played significant role in implementing the new ways in medical education. In universities mode of learning have been shifted from traditional face to face learning to online methods. The pre-clinical education is the backbone of medical carrier and knowledge of anatomy is essential for understanding the clinical subjects. Online teaching with innovative teaching strategies has now become an alternative source for students learning human anatomy. These changes will impact the future of anatomy education. After the pandemic over teaching and learning anatomy will be accomplished by use of both modern multimedia resources and conventional approach. During pandemic the mentorship may play key role in alleviating the academic stress and psychological issues in students.